Resilient and agile engineering solutions to address societal challenges such as coronavirus pandemic. (September 2020) - Goel, Saurav; Hawi, Sara; Goel, Gaurav; Thakur, Vijay Kumar; Agrawal, Anupam; Hoskins, Clare; Pearce, Oliver; Hussain, Tanvir; Upadhyaya, Hari M.; Cross, Graham; Barber, Asa H.
Abstract: The world is witnessing tumultuous times as major economic powers including the US, UK, Russia, India, and most of Europe continue to be in a state of lockdown. The worst-hit sectors due to this lockdown are sales, production (manufacturing), transport (aerospace and automotive) and tourism. Lockdowns became necessary as a preventive measure to avoid the spread of the contagious and infectious "Co ronavi rus D isease 2019" (COVID-19). This newly identified disease is caused by a new strain of the virus being referred to as S evere A cute R espiratory S yndrome Co ronaV irus 2 (SARS CoV-2; formerly called 2019-nCoV). We review the current medical and manufacturing response to COVID-19, including advances in instrumentation, sensing, use of lasers, fumigation chambers and development of novel tools such as lab-on-the-chip using combinatorial additive and subtractive manufacturing techniques and use of molecular modelling and molecular docking in drug and vaccine discovery. We also offer perspectives on future considerations on climate change, outsourced versus indigenous manufacturing, automation, and antimicrobial resistance. Overall, this paper attempts to identify key areas where manufacturing can be employed to address societal challenges such as COVID-19. Graphical abstract: Image 1 Highlights: We review the coronavirus pandemic and discuss salient aspects of the disease, its impact, propagation and treatment options. Nanotechnology and ultra-precision engineering hold the promise in developing resilient measures to tackle the pandemic. Digital manufacturing and automation can help productivity and modelling and simulation can aid drug and vaccine discovery. We explore design for manufacturing approaches required for developing new face masks and PPE's. We discuss the short- and long-term impact of COVID-19 on supply chains, climate change and lifestyles.